1997
DOI: 10.1016/s0035-9203(97)90083-3
|View full text |Cite
|
Sign up to set email alerts
|

Plasma nitrogen oxides and blood lactate concentrations in Ghanaian children with malaria

Abstract: Nitric oxide is an important host defence molecule as well as being a mediator in many pathophysiological processes. To investigate its role in severe malaria, we measured plasma nitrate and nitrite concentrations in 70 children with malaria (54 with severe malaria) and 48 control subjects (33 with medical conditions and 15 surgical patients). We related these measurements to plasma lactate concentrations, an established marker of disease severity in malaria. Plasma lactate levels were significantly elevated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 16 publications
3
31
1
Order By: Relevance
“…Data from humans are limited. Although a number of human clinical studies have shown an inverse relationship between parasitemia and plasma levels (Agbenyega et al, 1997;Kremsner et al, 1996), this has not been a consistent finding and the correlations have been at best modest. Moreover, the levels reported in the studies showing this inverse correlation were not controlled for potential confounding effects of diet and renal impairment.…”
Section: No and Host Protection In Vivomentioning
confidence: 92%
See 1 more Smart Citation
“…Data from humans are limited. Although a number of human clinical studies have shown an inverse relationship between parasitemia and plasma levels (Agbenyega et al, 1997;Kremsner et al, 1996), this has not been a consistent finding and the correlations have been at best modest. Moreover, the levels reported in the studies showing this inverse correlation were not controlled for potential confounding effects of diet and renal impairment.…”
Section: No and Host Protection In Vivomentioning
confidence: 92%
“…Measurement of nitrate + nitrite in plasma and urine provides a valid and useful marker of NO production in rodents and humans in a variety of disease states (Hibbs et al, 1992;Granger et al, 1996Granger et al, , 1999Anstey et al, 1996), provided there is adequate control for the potentially confounding effects of dietary nitrate ingestion and nitrate retention resulting from renal impairment. Although several studies have described plasma levels in human malaria (Cot et al, 1994;Nussler et al, 1994;Prada and Kremsner, 1995;Al Yaman et al, 1996;Kremsner et al, 1996;Agbenyega et al, 1997), it has been difficult to extrapolate NO production from the levels reported in these studies because of absent or insufficient numbers of disease-free control subjects and inadequate control for the potential confounding effects of dietary nitrate ingestion (Mitchell et al, 1916;Anonymous, 1981;Granger et al, 1996), renal impairment (Mackenzie et al, 1996;Anstey et al, 1997c), decreased fractional excretion of (Anstey et al, 1996), and altered volume of distribution of in malaria. Each of these confounders can act to increase plasma levels in malaria without reflecting increased NO production (Anstey et al, 1997c).…”
Section: No Methodology: Lessons From Malaria Field Studiesmentioning
confidence: 99%
“…91 Cerebrospinal fluid levels of NO x were not increased in Ghanaian children with CM, and there is no difference in those who die compared with the survivors. 92 At this point, detecting tissue expression of NO synthase immunohistochemically, or via in situ hybridization, may provide the most reliable measures of NO effects in fatal malaria.…”
Section: Pathophysiology Of Fatal Malariamentioning
confidence: 99%
“…Some authors have associated NO with severe and complicated malaria, particularly cerebral malaria (1,3,6,9,10,12,13,29), whereas other authors have argued that NO has a protective role (2,4,21,22,26,(34)(35)(36)(37)). An interesting contradiction concerning the role of NO in malaria emerged from two recent studies.…”
mentioning
confidence: 99%